2012
DOI: 10.1186/1472-6947-12-142
|View full text |Cite
|
Sign up to set email alerts
|

Intention to adopt clinical decision support systems in a developing country: effect of Physician’s perceived professional autonomy, involvement and belief: a cross-sectional study

Abstract: BackgroundComputer-based clinical decision support systems (CDSS) are regarded as a key element to enhance decision-making in a healthcare environment to improve the quality of medical care delivery. The concern of having new CDSS unused is still one of the biggest issues in developing countries for the developers and implementers of clinical IT systems. The main objectives of this study are to determine whether (1) the physician’s perceived professional autonomy, (2) involvement in the decision to implement C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 27 publications
(52 reference statements)
9
42
2
1
Order By: Relevance
“…The nding that performance expectancy is related to intention to use the new EMMS aligns with previous studies that claim performance expectancy is an important determinant of doctors' intention to use a new technology [26].The greatest bene t and also disbene t on performance expectancy for doctors was introduced by pre-de ned order sets. Our ndings are consistent with other studies that found a key facilitator for user-acceptance were order sentences that increased prescriber e cacy [11; 32] and evidence-based practices, [3; 17; 32].…”
Section: Discussionsupporting
confidence: 86%
“…The nding that performance expectancy is related to intention to use the new EMMS aligns with previous studies that claim performance expectancy is an important determinant of doctors' intention to use a new technology [26].The greatest bene t and also disbene t on performance expectancy for doctors was introduced by pre-de ned order sets. Our ndings are consistent with other studies that found a key facilitator for user-acceptance were order sentences that increased prescriber e cacy [11; 32] and evidence-based practices, [3; 17; 32].…”
Section: Discussionsupporting
confidence: 86%
“…37 The results of the present study showed that there is no significant relationship between performance expectancy and behavioral intention, and this is inconsistent with previous studies that claim the performance expectancy as an important determinant of users' intention to use a new technology. 52,53 This may be due to the poor familiarity of the medical students with health applications and health care services of mobile in medical science universities. Ultimately, the results of present study are not in line with the results of Hoque and Sorwar 37 and Schomakers et al 44 studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is because users are unlikely to anticipate benefits from a system that is perceived difficult to use [45]. Prior health IT acceptance studies support the effect of effort expectancy perceptions on performance expectancy (e.g., [40] [48]). Thus, we further hypothesise: H3.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%